2017
DOI: 10.5535/arm.2017.41.2.273
|View full text |Cite|
|
Sign up to set email alerts
|

Immediate Effect of a Single Session of Whole Body Vibration on Spasticity in Children With Cerebral Palsy

Abstract: ObjectiveTo investigate the immediate effect of a single session of whole body vibration (WBV) on lower extremity spasticity in children with cerebral palsy (CP).MethodsSeventeen children with spastic CP were included. A single session of WBV was administered: 10-minute WBV, 1-minute rest, and 10-minute WBV. The effects of WBV were clinically assessed with the Modified Ashworth Scale (MAS) and Modified Tardieu Scale (MTS) before and immediately, 30 minutes, 1 hour, 2 hours, 3 hours, and 4 hours after WBV.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…This phenomenon could be attributed to the trend of decreasing tendon stiffness after WBV in hemiparetic limbs and relative smaller changes in unaffected limbs. A previous study showed that a single 20 min session of WBV can reduce the spasticity of ankle plantar flexors for 1-2 h in children with cerebral palsy [27]. Another study revealed that a single session of WBV training appeared to successfully reduce ankle spasticity in stroke patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be attributed to the trend of decreasing tendon stiffness after WBV in hemiparetic limbs and relative smaller changes in unaffected limbs. A previous study showed that a single 20 min session of WBV can reduce the spasticity of ankle plantar flexors for 1-2 h in children with cerebral palsy [27]. Another study revealed that a single session of WBV training appeared to successfully reduce ankle spasticity in stroke patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, brief and localized encounters with vibration is analgesic and is known to reduce pain of such things as injections [ 3 ], acute headaches [ 4 ] and hair restoration procedures [ 5 ]. Clinically, vibration is also used in managing diseases such as meibomian gland dysfunction [ 6 ], cerebral palsy [ 7 , 8 ] and Parkinson’s disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A low frequency sound (below 100Hz) in the audible range can produce mechanical vibrations that are different from the infrasonic frequencies (below 20 Hz) that are not audible to the human ear. (Hooper J., 2002) By the term vibroacoustic therapy in literature is intended the sound-induced, low-frequency vibrations (not mechanical vibrations) mixed with music listening this kind of particular therapy could induce results also on the muscular system and in spasticity (Park C.,2017) Vibroacoustic therapy uses low-frequency sinusoidal sound in the 30-120 Hz range supplemented by music for therapeutic purposes (Wigram T., 1996). In the 1990, the physio acoustic method based on body scanning with a sinusoidal sound between 27-113 Hz and listening to specially selected music was developed by Lehikoinen (Boyd-Brewer C. H., 2003).…”
Section: Introductionmentioning
confidence: 99%